2008
DOI: 10.1534/genetics.107.079780
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Serotonin Biosynthesis by the G Proteins Gαo and Gαq Controls Serotonin Signaling inCaenorhabditis elegans

Abstract: To analyze mechanisms that modulate serotonin signaling, we investigated how Caenorhabditis elegans regulates the function of serotonergic motor neurons that stimulate egg-laying behavior. Egg laying is inhibited by the G protein Ga o and activated by the G protein Ga q . We found that Ga o and Ga q act directly in the serotonergic HSN motor neurons to control egg laying. There, the G proteins had opposing effects on transcription of the tryptophan hydroxylase gene tph-1, which encodes the rate-limiting enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(78 citation statements)
references
References 52 publications
3
75
0
Order By: Relevance
“…Consistent with this, we found that tph-1 expression was increased in goa-1(n1134) mutants (data not shown), as previously reported (10). As a first step toward confirming whether the hyperactive egg-laying behavior of str-33(ykp001) mutants was due to changed tph-1 expression in HSNs, we transfected these animals with a tph-1::gfp construct.…”
Section: Str-33 Suppresses 5-ht Biosynthesis In Hsns Throughsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with this, we found that tph-1 expression was increased in goa-1(n1134) mutants (data not shown), as previously reported (10). As a first step toward confirming whether the hyperactive egg-laying behavior of str-33(ykp001) mutants was due to changed tph-1 expression in HSNs, we transfected these animals with a tph-1::gfp construct.…”
Section: Str-33 Suppresses 5-ht Biosynthesis In Hsns Throughsupporting
confidence: 88%
“…Unexpectedly, str-33 was not expressed in HSNs or VC neurons, which are directly involved in egg-laying behavior (6,10). However, it was detected in ALM and PLM mechanosensory neurons and head neurons (Fig.…”
Section: Isolation and Basic Characterization Of The Str-33mentioning
confidence: 91%
See 2 more Smart Citations
“…In vertebrates, serotonin is produced from the essential aromatic amino acid tryptophan via the neuroactive compound 5-hydroxytryptophan (5-HTP) by first a hydroxylation reaction catalyzed by tryptophan hydroxylase (TPH), which is then followed by decarboxylation by aromatic amino acid decarboxylase (AADC) [14] . Similarly, plants first synthesize tryptophan via the chorismate pathway which is then decarboxylated by tryptophan decarboxylase (TDC) to form tryptamine, another bioactive amino acid and common secondary metabolite precursor.…”
Section: Serotonin Biosynthesismentioning
confidence: 99%